Annealing Effects on the Crystallinity of Carbon Fiber-Reinforced Polyetheretherketone and Polyohenylene Laminate Composites Manufactured by Laser Automatic Tape Placement - Svetlana RISTESKA; Anka T. PETKOSKA; Samoil SAMAK; Marian DRIENOVSKY (Medžiagotyra)
In situ consolidation of thermoplastic composites by Automated Tape Placement (ATP) is challenging. High quality ATP grade pre-preg material and tape head equipped with an efﬁcient heat sources like lasers offer an opportunity towards high deposition rates and improved mechanical properties of composite materials. In this study uni-directional carbon fiber/ polyphenylene sulfide (UD tape prepreg CF/PPS), carbon fiber/polyetheretherketone (UD tape prepreg CF/PEEK) as well as blend of carbon fiber/polyetheretherketone/polyphenylene sulfide (UD tapes prepregs CF/PEEK/PPS) laminates are compared in terms of their properties after beeing processed by ATP technology. CF/PPS, CF/PEEK and blend CF/PPS/PEEK laminate specimens were processed using in-situ laser-assisted ATP (LATP) process. LATP processing parameters used in this study were chosen based on a preliminary trials; the results provide a basis for reﬁnement of these parameters and prepreg material with an optimal and balanced set of final mechanical properties. This study showed an attempt how to manage the processing parameters for LATP process and to obtain composite materials with tailored properties. The process for production of thermoplastic plates with LATP head in general is a process that is governed by many parameters such as: laser power, angle of incidence, roller pressure and temperature, placement speed, tool temperature, then types of the roller material and the tool material. These parameters are not subject of discussing in this paper; they are kept constant, and the goal of the paper is to manage the crystallinity level within the composite thermoplastic material during annealing step at different temperatures after LATP process. Also, the void content during the production process could be controlled. More particularly, the authors showed that composites based on PPS matrix manufactured with LATP process possess higher flexural strength, with less void content compared to samples based on PEEK matrix. These samples showed also higher crystallinity after annealing step.